2019
DOI: 10.1371/journal.pone.0215827
|View full text |Cite
|
Sign up to set email alerts
|

Impact of various types of near work and time spent outdoors at different times of day on visual acuity and refractive error among Chinese school-going children

Abstract: Background Various types of near work have been suggested to promote the incidence and progression of myopia, while outdoor activity appears to prevent or retard myopia. However, there is a lack of consensus on how to interpret these results and translate them into effective intervention strategies. This study examined the association between visual acuity and time allocated to various activities among school-going children. Methods Population-based survey of 19,934 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 31 publications
2
89
3
4
Order By: Relevance
“…Although we found no significant association between screen time and myopia in the meta‐analysis, these results are not convincing evidence of the link between digital devices and myopia, due to the low number of studies included. In the review results we found that the more recent studies seem to show a trend of association that might be related with the increase in screen time for the more recent years. However, this is expected given the introduction and rise in screen time in children, and this trend should be critically evaluated as educational near work may now be primarily screen time in origin instead of traditional "paper and pen” with a substitution effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we found no significant association between screen time and myopia in the meta‐analysis, these results are not convincing evidence of the link between digital devices and myopia, due to the low number of studies included. In the review results we found that the more recent studies seem to show a trend of association that might be related with the increase in screen time for the more recent years. However, this is expected given the introduction and rise in screen time in children, and this trend should be critically evaluated as educational near work may now be primarily screen time in origin instead of traditional "paper and pen” with a substitution effect.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies included in this review published in 2014 and above show positive associations (five out of seven studies; Figure ). Positive associations where reported in children (aged 5–16 years) from Vietnam in 2014, India in 2015 and 2017 and China in 2016 and 2019 …”
Section: Discussionmentioning
confidence: 99%
“…Having at least 60 minutes of daily exercise [ 23 ] or one additional hour of outdoor time per week [ 26 ] could reduce the odds of a child having myopia. In addition, children who spent time outdoors at mid-day for 31–60 minutes or more than 60 minutes had better uncorrected visual acuity than students who spent less time outdoors [ 27 ]. However, other studies found that outdoor activities had less of a protective effect on myopia [ 6 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…function, 9 sleep, 2 typical behaviours, 5,10 play, 11 the way they interact with their mothers 7,8,[12][13][14] and possibly their vision. 15 Parenting styles, caregiving behaviours and mother-child interactions have been demonstrated to influence children's screen time, especially background media exposure. [16][17][18] This paper refers to three types of parenting styles.…”
mentioning
confidence: 99%